Climate Change Attitudes, Beliefs and Intentions Among Young Adults In an Institution of Higher Learning: Does Personality Matter?
The present article is concerned with the relationships between personality traits and climate change attitudes, beliefs and intentions. This was done to determine the relationship that exists between personality traits and attitudes, beliefs and intentions towards climate change issues. A descriptive survey design was used in conducting this study. The sample comprised 203 undergraduate students (116 males and 87 females) selected from various Faculties in Obafemi Awolowo University, Ile-Ife, Nigeria. Convenience sampling technique was used to collect data from the respondents. Their age ranged from 15 to 35 years (M=23.6; SD=5.2). The Big Five Personality Inventory (BFPI) and the Climate Change Attitude Survey (CCAS) were used to collect data from participants. Results revealed that the vast majority of participants agree or strongly agree that human activities cause global climate change. (46% and 37.4% respectively). Furthermore, the results showed that there is a significant influence of personality dimensions on climate change attitudes, beliefs and intentions (F (5,195) =20.327, p<.05